Effectiveness of complementary therapies for the management of symptom clusters in palliative care in pediatric oncology: a systematic review - Lopes-Júnior, Luís Carlos; Urbano, Isadora Rangel; Schuab, Sara Isabel Pimentel de Carvalho; Pessanha, Raphael Manhães; Rosa, Gabriela Sylvestre; Lima, Regina Aparecida Garcia de (Revista da Escola de Enfermagem da USP, 2021)
Objective: To evaluate the effectiveness of complementary therapies in the management of symptom clusters in children and adolescents with cancer undergoing palliative care. Method: Systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, resorting to the databases MEDLINE, Web of Science, Central Cochrane, and PsycINFO. The identification, selection, inclusion, extraction, and methodological assessment were conducted by two independent reviewers. Results: Five quasi-experiments met the eligibility criteria. The heterogeneous characteristics of the studies made meta-analysis impossible. Two studies used therapeutic massage, one used Reiki, one used boswellic acid, and one used Cannabis sativa; three of them (therapeutic massage and Reiki) presented statistically significant results for the management of the cluster pain-anxiety-worry-dyspnea. Most studies presented a moderate risk of bias as per ROBINS-I tool. Conclusion: Therapeutic massage and Reiki may be effective for the symptom clusters management, especially the pain-anxiety-worry-dyspnea cluster in children and adolescents undergoing palliative care.